Oxymatrine Synergistically Enhances Doxorubicin Anticancer Effects in Colorectal Cancer - Pan, Di; Zhang, Wen; Zhang, Nenling; Xu, Yini; Chen, Yi; Peng, Jianqing; Chen, Yan; Zhang, Yanyan; Shen, Xiangchun (Frontiers in Pharmacology, 2021)
Abstract The combination of chemotherapy with natural products is a common strategy to enhance anticancer effects while alleviating the dose-dependent adverse effects of cancer treatment. Oxymatrine (OMT) has been extensively reported as having anticancer activity. Doxorubicin (DOX) is a chemotherapeutic DNA damaging agent used for the treatment of carcinoma. In this study, we investigated whether synergistic effects exist with the combination treatment with OMT and DOX using human colorectal cancer cells (CRC) lines and the potential mechanisms involved in vitro and in vivo activities. The MTT and colony formation assay results showed that compared to either OMT or DOX monotherapy, the combination of OMT+DOX markedly inhibited the growth of HT-29 and SW620 cells. Wound healing assays showed significant inhibition of cell migration under co-treatment, supported by the change of E-cadherin and N-cadherin expression in western blotting. Furthermore, flow cytometry analysis revealed that OMT+DOX co-treatment enhanced cell apoptosis as a result of ROS generation, whereas NAC attenuated OMT+DOX-induced apoptosis. Similarly, the apoptotic-related proteins (cleaved caspase-3, cleaved caspase-9, and the ratio of Bax/Bcl-2) were determined by western blotting, which showed that the expression of these markers were notably increased in the co-treatment group. Furthermore, co-administration of a low dose of DOX and OMT inhibited xenografte tumor growth in a dose-dependent manner. TUNEL assay and Ki67 staining images indicated more apoptosis and less proliferation occurred in OMT plus DOX-treated xenograft tumors. Meanwhile, the combination strategy decreased cardiotoxicity, which is the most serious side effect of DOX. RNA-sequencing was performed to explore the precise molecular alterations involved in the combination group. Among the numerous differentially expressed genes, down-regulated FHL2 and up-regulated cleaved SPTAN1 were validated in both mRNA and protein levels of HT-29 and SW620 cells. These two proteins might play a pivotal role involving in OMT+DOX synergistic activity. Overall, OMT in combination with DOX presented an outstanding synergistic anti-tumor effect, indicating that this beneficial combination may offer a potential therapy for CRC patients.